Back Cover: Three‐Dimensional Carbon‐Coated SnO2/Reduced Graphene Oxide Foam as a Binder‐Free Anode for High‐Performance Lithium‐Ion Batteries (ChemElectroChem 7/2016). Issue 7 (27th June 2016) - Tao, Huachao; Zhu, Shouchao; Xiong, Lingyun; Yang, Xuelin; Zhang, Lulu
Abstract : The Back Cover picture shows carbon‐coated SnO2 nanoparticles/reduced graphene oxide foam, which exhibits high reversible capacity and excellent cycling performance as the anode for lithium‐ion batteries. The carbon layer could enhance the bonding strength of SnO2 nanoparticles and reduced oxide graphene. More information can be found in the Full Paper by X. Yang and co‐workers onpage 1063 in Issue 7, 2016 (DOI:10.1002/celc.201600128 ).